2021
DOI: 10.1186/s12905-021-01514-y
|View full text |Cite
|
Sign up to set email alerts
|

Using geographically weighted Poisson regression to examine the association between socioeconomic factors and hysterectomy incidence in Wallonia, Belgium

Abstract: Background Various studies have investigated geographical variations in the incidence of hysterectomy in Western countries and analyzed socioeconomic factors to explain those variations. However, few studies have used spatial analysis to characterize them. Geographically weighted Poisson regression (GWPR) explores the spatially varying impacts of covariates across a study area and focuses attention on local variations. Given the potential of GWPR to guide decision-making, this study aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is important to understand the local spatial differences across a region when developing and assessing healthcare policies. To address this issue, studies have started using the geographically weighted Poisson regression (GWPR) method to map spatial variations in these relationships (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to understand the local spatial differences across a region when developing and assessing healthcare policies. To address this issue, studies have started using the geographically weighted Poisson regression (GWPR) method to map spatial variations in these relationships (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the local spatial differences across a region when developing and assessing healthcare policies. To address this issue, studies have started using the geographically weighted Poisson regression (GWPR) method to map spatial variations in these relationships (15–18). To the best of our knowledge, no study has reported on the distribution of adult CIs in relation to the sociodemographic factors of different regions using GWPR in a two-tier or single-payer healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of hysterectomy might be for non-oncologic diseases. Some studies have suggested that ethnic/racial differences are related to hysterectomy [ 9 , 10 , 11 ]. However, income and education level have not been studied in detail yet.…”
Section: Introductionmentioning
confidence: 99%